KONDISI FISIK DENGAN MPN COLIFORM AIR SUMUR GALI DI KELURAHAN BITUNG BARAT SATU KOTA BITUNG - Haslinda Pontoh; Jusran Mokoginta; Agnes T. Watung (Jurnal Kesehatan Lingkungan, 2018)
The quality of water consumed by the community can determine the degree of health of the community. The quality of clean water used by the community is greatly influenced by the quality of the water source besides the type of water source used. The number of diarrhea cases in Bitung City according to the results of the 2013 North Sulawesi Riskesdas was 3.4. The purpose of this study was to determine the relationship between the Physical Condition of Dug Wells and MPN Coliform Air Dug Wells in Kelurahan Bitung Barat. This research was an analytic observational study using a cross sectional study design. The population in this study amounted to 112 wells, with a sample of 31 wells chosen at random. Data collection was carried out through interviews, observations and laboratory examinations of dug well water samples. Data were analyzed bytest Chi-Square. The results of this study indicate the physical condition of dug wells that did not meet the requirements of 24 (77.42%) wells with 18 (75%) of them containing> 50 MPN Coliform/ 100 ml or not fulfilling the requirements while 7 (22.58%) wells were physical condition fulfills the requirements of 4 (57.14%) of which contain> 50 MPN Coliform/ 100 ml or do not meet the requirements and so the number of wells with MPN Coliform does not meet the requirements of 22 (70%) wells. Statistical test results using thetest chi-square obtained p value = 0.360> 0.05 meaning that there is no significant relationship between the physical condition of dug wells with MPN coliform dug well water in West Bitung Village. Conclusion: The research results prove that there is no significant relationship between the physical condition of dug wells with MPN Coliform, but in general the bacteriological conditions of dug wells have not met the requirements and are not suitable to be used as a source of clean water therefore it is necessary to improve environmental sanitation conditions around wells dug and still pay attention to the physical condition of the well.